Environmental monitoring with Arduino - Gertz, Emily (Cahiers de projets., 2012)
After the devastating tsunami in 2011, DYIers in Japan built their own devices to detect radiation levels, then posted their finding on the Internet. Right now, thousands of people worldwide are tracking environmental conditions with monitoring devices they've built themselves. You can do it too! This inspiring guide shows you how to use Arduino to create gadgets for measuring noise, weather, electromagnetic interference (EMI), water purity, and more. You'll also learn how to collect and share your own data, and you can experiment by creating your own variations of the gadgets covered in the book. If you're new to DIY electronics, the first chapter offers a primer on electronic circuits and Arduino programming.